Bioprocessing of Brewers’ Spent Grain Enhances Its Antioxidant Activity: Characterization of Phenolic Compounds and Bioactive Peptides - Verni, Michela; Pontonio, Erica; Krona, Annika; Jacob, Sera; Pinto, Daniela; Rinaldi, Fabio; Verardo, Vito; Díaz-de-Cerio, Elixabet; Coda, Rossana; Rizzello, Carlo Giuseppe (Frontiers in Microbiology, 2020)
Brewers’ spent grain (BSG) is the major by-product of the brewing industry which remain largely unutilized despite its nutritional quality. In this study, the effects of fermentation on BSG antioxidant potential were analyzed. A biotechnological protocol including the use of xylanase followed by fermentation with Lactiplantibacillus plantarum (Lactobacillus plantarum) PU1, PRO17 and H46 was used. Bioprocessed BSG exhibited enhanced antioxidant potential, characterized by high radical scavenging activity, long-term inhibition of linoleic acid oxidation and protective effect towards oxidative stress on human keratinocytes NCTC 2544. Immunolabelling and confocal laser microscopy showed that xylanase caused an extensive cell wall arabinoxylan disruption, contributing to the release of bound phenols molecules, thus available to further conversion through lactic acid bacteria metabolism. To clarify the role of fermentation on the antioxidant BSG potential, phenols were selectively extracted and characterized through HPLC-MS techniques. Novel antioxidant peptides were purified and identified in the most active bioprocessed BSG.